PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBERED HEADS TOGETHER) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD INPRES BERTINGKAT LABUANG BAJI KOTA MAKASSAR - Wahyullah Alannasir (Fakultas Keguruan dan Ilmu Penidikan UIM, 2019)
Abstract: The Application of NHT (Numbered Heads Together) Cooperative Learning Model to Improve Mathematics Learning Outcomes of Class V Student of SD Inpres Bertingkat Labuang Baji Makassar. This study aimed to increase in the quality of teaching and learning process for class V students of SD Inpres Bertingkat Labuang Baji Makassar, and improve mathematics learning achievement for SD Inpres Bertingkat Labuang Baji Makassar by implementing NHT (Numbered Head Together) cooperative learning. The research method used the type of Classroom Action Research. The focus of this study was the NHT type of cooperative learning model, and Mathematics learning outcomes. The subjects in this study were Class V students with a total of 38 students. The procedures of this research included: planning, implementing, acting, observing, and reflecting. Data collection techniques and research instruments were observation, test and documentation. The data analysis technique used descriptive analysis. The result showed that the results of the first cycle test, student learning outcomes were in enough category and had not reached the expected learning completeness. Then the second cycle became good category, and achieved the expected learning completeness. Improving student learning outcomes through the use of the NHT type of cooperative learning model was supported by an increase in student activity in the following the lessons, in the form of: discipline in group formation, activeness in problem discussion, regularity in numbering members (exchanging answers in groups), and concluding mathematics subject matter. It could be concluded that the application of the NHT type of cooperative learning model could improve the learning outcomes of class V students of SD Inpres Bertingkat Labuang Baji Makassar.Keywords: NHT Type Cooperative Model, Mathematics Learning Outcomes